Socialization of Healthcare Service Innovation: Developing a Pharmacy Information System to Improve Access and Service Quality - Dadang Muhammad Hasyim; Arief Budi Pratomo; Abdul Rosid; Novycha Auliafendri; Ramson Rikson Maruwahal Sijabat (PT. Global Research Collaboration, 2025)
Effective pharmacy management is essential in ensuring drug availability in health facilities. This study aims to analyze the pharmaceutical management system in Garut Regency, focusing on aspects of recording, infrastructure, readiness of health workers, and local government policies. The research method used was a qualitative approach with interview and observation techniques in several health facilities. The results showed that many health facilities still use a manual recording system, which risks causing errors and delays in drug procurement. In addition, limited infrastructure and the readiness of health workers in adopting pharmaceutical information systems are the main obstacles in digitizing pharmaceutical management. In terms of policy, the absence of strong regulations and limited budget hamper the optimal implementation of digital systems. Therefore, it is necessary to improve infrastructure, train health workers, and support clearer policies to encourage the digitalization of the pharmaceutical system in Garut Regency.